ECONOMIC GROWTH IN THE CENTRAL CAUCASO-ASIAN COUNTRIES ADJUSTED FOR THE CATCH-UP EFFECT - PAPAVA, Vladimer (CENTRAL ASIA AND THE CAUCASUS, 2012)
One of the main problems of economic development is to ensure stable economic growth. This article examines some issues relating to the measurement of economic growth in the context of Central Caucaso-Asia, a geopolitical region which includes the countries of the Central Caucasus (Azerbaijan, Armenia and Georgia) and Central Asia (Kazakhstan, Kyrgyzstan, Tajikistan, Turkmenistan and Uzbekistan). It should be emphasized that this problem has been analyzed in a number of significant publications.2 In order to measure economic growth, it is particularly important to use a more or less adequate method allowing a spatial comparison of countries and regions. But at present such a comparison is complicated by the existence of the so-called “catch-up effect.”